Deskripsi Sistem Divisi Jurusan Antara Sekolah Indonesia dan Sekolah Menengah Kebangsaan Malaysia - Zakirman Zakirman; Wienda Gusta; Chichi Rahayu (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
This study aims to describe the comparison of departmental distribution systems in secondary schools in Indonesia and Malaysia. This type of research is descriptive, the research instrument used is the observation sheet and document documentation when conducting field visits to sample schools in Indonesia and Malaysia. Conclusions from the results of this study include differences in departmental distribution systems with striking differences, namely in Indonesia schools can classify students based on majors at grade X level, while in Malaysia, grouping majors starts at grade 4 at the secondary school level. In addition, the basic curriculum differences that students must take also can be clearly seen and differ significantly.